Research on the influencing factors of subjective well-being of Chinese college students based on panel model - Qin, Ting; Wei, Pingqiang; Zhu, Chengyi (Frontiers in Psychology, 2024)
The subjective well-being of Chinese college students has always been a topic of concern.Subjective well-being is an overall evaluation of the quality of life according to the standards set by individuals, which is of great significance to the development of college students. Based on the data published in the past five years of China 's comprehensive social survey, this study uses panel model and adversarial explanatory structure model to analyze the influencing factors of subjective well-being of Chinese college students from five dimensions: social equity attitude, parental education, use of network, social interaction and physical health. The results show that social justice attitude, parents ' education, network use, social interaction and physical health have a positive impact on the subjective well-being of Chinese college students. Among them, the use of the network and the education of parents mainly affect the social justice attitude, social interaction attitude, physical health status, and ultimately affect the subjective well-being of college students.Based on the above conclusions, this study proposes strategies to improve the subjective well-being of college students, which has certain reference and guiding significance for educators and decision makers, and has reference significance for developing countries.